Fundamentals of Ultrasonic Nondestructive Evaluation A Modeling Approach - Schmerr Jr., Lester W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This extensively revised and updated second edition of a widely read classic presents the use of ultrasound in nondestructive evaluation (NDE) inspections. Retaining the first edition's use of wave propagation /scattering theory and linear system theory, this volume also adds significant new material including: the introduction of MATLAB® functions and scripts that evaluate key results involving beam propagation and scattering, flaw sizing, and the modeling of ultrasonic systems. elements of Gaussian beam theory and a multi-Gaussian ultrasonic beam model for bulk wave transducers. a new chapter on the connection between ultrasonic modeling and probability of detection (POD) and reliability models. new and improved derivations of ultrasonic measurement models. updated coverage of ultrasonic simulators that have been developed around the world. Students, engineers, and researchers workingin the ultrasonic NDE field will find a wealth of information on the modeling of ultrasonic inspections and the fundamental ultrasonic experiments that support those models in this new edition.
An Ultrasonic System -- Linear Systems and the Fourier Transform -- Wave Motion Fundamentals -- Propagation of Bulk Waves -- The Reciprocal Theorem and Other Integral Relations -- Reflection and Transmission of Bulk Waves -- Propagation of Plate and Surface Waves -- Ultrasonic Transducer Radiation -- Material Properties and System Function Determination -- Flaw Scattering -- The Transducer Reception Process -- Ultrasonic Measurement Models -- Near Field Measurement Models -- Quantitative Ultrasonic NDE With Models -- Model-Based Flaw Sizing -- Probability of Detection and Reliability -- Appendix A. The Fourier Transform -- Appendix B. The Dirac Delta Function -- Appendix C. Basic Notations and Concepts -- Appendix D. The Hilbert Transform -- Appendix E. The Method of Stationary Phase -- Appendix F. Properties of Ellipsoids -- Appendix G. MATLAB Functions and Scripts.
Keywords: Materials -- Analysis; Mechanics, Applied; Solids; Physics; Ultrasonics; Engineering mathematics; Engineering -- Data processing; Acoustics; Characterization and Analytical Technique; Solid Mechanics; Classical and Continuum Physics; Ultrasonics; Mathematical and Computational Engineering Applications; Acoustics